Synergistic modulation of local environment for electrochemical nitrate reduction via asymmetric vacancies and adjacent ion clusters. (July 2022) - Chen, Dong; Zhang, Shaoce; Bu, Xiuming; Zhang, Rong; Quan, Quan; Lai, Zhengxun; Wang, Wei; Meng, You; Yin, Di; Yip, SenPo; Liu, Chuntai; Zhi, Chunyi; et al.
Abstract: Electrochemical conversion of nitrate to ammonia is widely considered a "two birds with one stone" approach to alleviate the nitrate pollution in water and simultaneously to generate the valuable green NH3 fuels. However, it remains challenging due to the lack of efficient electrocatalysts for practical utilization. Herein, we investigate the synergistic effect between asymmetric Cu-Ov -W sites (Ov represents oxygen vacancy) and adjacent Mo clusters in tuning the local electronic environment around active sites of catalysts for substantially enhanced nitrate reduction. The dynamic balance between the adsorption and desorption of O in NO3 - caused by asymmetric Ov and the promoted protonation process due to Mo clusters are responsible for boosting the entire process. Such synergistic effect modulates the local electronic environment for binding the reaction intermediates and dramatically facilitates the intermediate formation in rate-determining steps (*NO→*NOH and *NOH→*N), leading to the high NH3 Faradaic efficiency and yield rate of 94.60% and 5.84 mg h −1 mgcat. −1 at − 0.7 V vs. RHE, respectively. Graphical Abstract: ga1 Highlights: Plasma method was applied to control the concentration of oxygen vacancies. Oxygen vacancies act as active sites for the adsorption and activation of NO3 - . Asymmetric vacancies balance the adsorption and desorption of O in NO3 -, facilitating the formation of *N intermediate. Mo clusters accelerate the protonation process, leading to a relatively lower energy in the rate-determining step (*NO→*NOH). The synergistic effect of asymmetric Cu-Ov-W and adjacent Mo clusters modulates the local electronic environment.